2012
DOI: 10.7314/apjcp.2012.13.2.521
|View full text |Cite
|
Sign up to set email alerts
|

Low Microsomal Epoxide Hydrolase Expression is Associated with Bladder Carcinogenesis and Recurrence

Abstract: Microsomal epoxide hydrolase (mEH) plays a significant role in the metabolism of numerous xenobiotics and is associated with several forms of cancer. Here, we investigated the role of mEH expression in bladder carcinogenesis, subsequent progression and recurrence. The expression of mEH was analyzed by Western blot in 50 bladder urothelial carcinoma and 20 normal epithelial tissues. There was a significantly higher mEH expression in the normal epithelium (P<0.05) and mEH expression was lower in high stage than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These polymorphisms have been shown to be connected with prostate cancer, colorectal cancer, and bladder cancer. [3][4][5] In different studies it has been suggested that lung cancer and breast cancer are associated with risk. However, the results are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms have been shown to be connected with prostate cancer, colorectal cancer, and bladder cancer. [3][4][5] In different studies it has been suggested that lung cancer and breast cancer are associated with risk. However, the results are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…These polymorphisms may be associated with prostate cancer, colorectal cancer, and bladder cancer (Mittal and Srivastava, 2007;Liu et al, 2012;Zhang et al, 2012). Previous studies have suggested that the EPHX1 Tyr113His polymorphisms associated with the risk for lung cancer and breast cancer.…”
Section: Introductionmentioning
confidence: 99%